Suitable Cost-Effective Foundation Selection Approach Of Medium Height Buildings On Sandy Silt And Silt Clay Soils In Adama City - Shimelis, Regassa (ASTU, 2024)
Predicting a suitable cost-effective foundation type during the early stages of foundation design is a difficult task for geotechnical engineers as the cost is known only after finishing the design of foundations. This study presents the influence and prediction method of suitable cost-effective foundation type during early stages of foundation design for medium rise (G+10) buildings on typical sandy clay and sandy silt soils stratum in Adama city. Analysis of super structure to generate forces and moments, and sub structure foundation design done by CSI ETABS and Safe software respectively. Geotechnical property of soils like Atterberg limits test, Particle size distribution, standard proctor compaction and standard penetration test (SPT) were identified using laboratory and field tests. Overall costs of foundation were calculated from quantities and corresponding unit rate of structural and nonstructural foundation elements. Finally, an attempt is made to develop suitable method by multiple regression through computer program SPSS software. From the comparative analysis that has been made in this study, it was generally found that, design engineers have got an optional solution in foundation type selection at the same time saving design time.
Keywords: Bearing capacity, cost-effective foundation type selection, Modulus of Subgrade Reaction, Cost estimation